Semantic Comprehension, Inference and Psychological Externalism. (1st April 2013) - Owens, Joseph I.
Abstract: The externalist examples of Burge, Putnam etc. were offered as examples of how it is physically identical twins can differ in mental states such as belief, and little attention was paid to the interpretations the twins impose on their respective acoustic inputs. The received story today is that this form of interpretation—the semantic reading one assigns the sounds one hears—is the product of inference. The problem for this inferential model is simple to state: though the twins are physical doppelgangers and don't differ in their acoustic inputs, they differ in the interpretations they impose on their respective inputs. I argue that the inferential model does not allow for how it is the twins arrive at these different interpretations. And, since the externalist examples are compelling, this tells against the inferential model.